Influence of wood surface chemistry on the tensile and flexural properties of heat-treated mangrove/high-density polyethylene composites - Adebayo, Ganiyat Olusola; Hassan, Aziz; Yahya, Rosiyah; Rahman, Normasmira Abd; Lafia-Araga, Ruth Anayimi (Springer Verlag (Germany), 2019)
Mangrove wood fiber (MF) was treated at four different temperatures (120 °C, 140 °C, 160 °C and 180 °C) in order to improve its compatibility with polymer matrix. The chemo-structural, thermal and morphological characteristics of untreated and treated MF were analyzed. The chemical composition of the treated MF showed an increase in cellulose content from 46 to 56% at 120 °C, which decreased at further heating. The non-cellulosic constituents of the fiber were removed as indicated by the reduction in magnitude of absorbance peaks mainly at 3343 cm−1 and 1027 cm−1 in Fourier transform infrared spectroscopy. The X-ray diffraction depicted increased crystallinity with increased temperature due to the conversion of amorphous cellulose and some hemicelluloses to crystalline structures. Color spectroscopy showed higher values of lightness (L*) at 120 °C and 140 °C, with a corresponding increase in chroma coordinate a* and decrease in b* due to the chemical changes that occurred during the heat treatment. Surface morphology by field emission scanning electron microscopy revealed that heat treatment exposed the inner fibrillar feature of fiber, thereby increasing the roughness of the fiber surface. Thermogravimetry analysis further indicated that heat-treated MFs are more stable. Heat treatment improved the tensile strength and modulus of composites as fiber loading increased, while the flexural strength and modulus also showed the same trend. SEM images of tensile fractured surface indicated that the interfacial interaction between the matrix and untreated MF is weaker than the heat-treated specimens. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.